The efficacy of herbs as complementary and alternative therapy in recovery and clinical outcome among people with Covid-19: a systematic review, meta-analysis, and meta-regression - Komariah, Maria; Amirah, Shakirah; Maulana, Sidik; Abdurrahman, Muhammad Fahd; Ibrahim, Kusman; Platini, Hesti; Lele, Juan Alessandro Jeremis Maruli Nura; Kohar, Kelvin; Rahayuwati, Laili; Firdaus, Mohd Khairul Zul Hasymi (Dove Medical Press, 2023)
Background: The COVID-19 pandemic continues, and this condition has caused many cases in various countries around the world, resulting in more than 6 million deaths worldwide. Herbal medicines can act as immunomodulators, anti-inflammatories, antioxidants, antimicrobials, and others depending on the type and content of the herbs used. Previous studies have shown that several types of herbs, such as Echinacea purpurea, Curcumin or Turmeric, Nigella sativa, and Zingiber officinale, have proven their effectiveness as herbal plants for COVID-19. Methods: We conducted a comprehensive literature search through five databases, namely, PubMed, Scopus, Embase, Wiley, and ProQuest to assess the efficacy of phytopharmaceuticals until July 12, 2022. We used the Cochrane RoB 2.0 for the quality assessment of the study. Results: Phytopharmaceuticals significantly improved patients’ recovery rate (OR = 3.54; p < 0.00001) and reduced deaths (OR = 0.24; p < 0.0001) compared to the control group. Phytopharmaceuticals also performed as a protective factor for COVID-19 clinical symptoms, such as dyspnea (OR = 0.42; p < 0.05) and myalgia (OR = 0.31; p = 0.02) compared to the control group. However, there is no statistically significant effect on cough (OR = 0.76; p = 0.61) and fever (OR = 0.60; p < 0.20). The results were not affected by patients’ covariates [hypertension, diabetes mellitus, and cardiovascular diseases (meta-regression p > 0.05)]. Conclusion: Herbal medicine has the potential as an adjuvant therapy in the management of COVID-19.